The inflammatory injury in the striatal microglia-dopaminergic-neuron crosstalk involved in Tourette syndrome development - Wang, Xueming; Liu, Xiumei; Chen, Liangliang; Zhang, Xiaoling (Frontiers in Immunology, 2023)
Background Tourette syndrome (TS) is associated with immunological dysfunction. The DA system is closely related to TS development, or behavioral stereotypes. Previous evidence suggested that hyper-M1-polarized microglia may exist in the brains of TS individuals. However, the role of microglia in TS and their interaction with dopaminergic neurons is unclear. In this study, we applied iminodipropionitrile (IDPN) to establish a TS model and focused on the inflammatory injury in the striatal microglia-dopaminergic-neuron crosstalk. Methods Male Sprague–Dawley rats were intraperitoneally injected with IDPN for seven consecutive days. Stereotypic behavior was observed to verify the TS model. Striatal microglia activation was evaluated based on different markers and expressions of inflammatory factors. The striatal dopaminergic neurons were purified and co-cultured with different microglia groups, and dopamine-associated markers were assessed. Results First, there was pathological damage to striatal dopaminergic neurons in TS rats, as indicated by decreased expression of TH, DAT, and PITX3. Next, the TS group showed a trend of increased Iba-1 positive cells and elevated levels of inflammatory factors TNF-α and IL-6, as well as an enhanced M1-polarization marker (iNOS) and an attenuated M2-polarization marker (Arg-1). Finally, in the co-culture experiment, IL-4-treated microglia could upregulate the expression of TH, DAT, and PITX3 in striatal dopaminergic neurons vs LPS-treated microglia. Similarly, the TS group (microglia from TS rats) caused a decreased expression of TH, DAT, and PITX3 compared with the Sham group (microglia from control rats) in the dopaminergic neurons. Conclusion In the striatum of TS rats, microglia activation is M1 hyperpolarized, which transmits inflammatory injury to striatal dopaminergic neurons and disrupts normal dopamine signaling.